Development Of E-LKPD Based On The SSCS (Search, Solve, Create, and Share) Model In Science Lessons For Class V Students In Elementary School - Indah Hanifah Munawaroh (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
This study aims to develop an E-LKPD product based on the SSCS Model (Search, Solve, Create, and Share) in science subjects for fifth grade elementary school students. This study uses the Research and Development (R&D) method with a 4D development model. Research respondents were teachers and students of fifth grade elementary school. Data collection techniques in this study were carried out through interview instruments, questionnaires, observation, and documentation. The data analysis technique used descriptive qualitative and quantitative analysis. The results of this study indicate that the feasibility value by media experts gets a percentage of 93.75% in the very feasible category, the feasibility value by linguists gets a percentage of 80% in the appropriate category, and the feasibility value of material experts gets a percentage of 92.5% with the appropriate category. very worthy. Furthermore, the small group trial response showed 91.67% results or in other words the students gave a positive response. This shows that the E-LKPD based on the SSCS (Search, Solve, Create, and Share) model is very suitable for use in science subjects in fifth grade elementary school.